2006
DOI: 10.1111/j.1439-0388.2006.00566.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional effect of haemoglobin polymorphism on the haematological pattern of Gentile di Puglia sheep

Abstract: The relationship between haemoglobin polymorphism and haematological pattern were studied in Gentile di Puglia, the Apulia Merino native breed. In a sample of 292 individuals, on five different farms, alpha- and beta-globin genetic polymorphism was investigated. A remarkable polymorphism was detected especially at alpha-globin gene where the variations concerned both the quality of the gene product and gene expression. Triplicated and quadruplicated alpha-globin genes were observed in 8.6% and 1.2% of the alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…As a consequence, the considered breeds may represent a good model to investigate the molecular basis underlying tolerance to A. ovis . In particular, the unusual haemoglobin polymorphism recorded in Altamurana [6] as well as the other Apulian native sheep breeds [7,12] and the related functional effects may have an adaptive significance related to the local selective pressure exerted by the pathogen and therefore deserve closer examination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the considered breeds may represent a good model to investigate the molecular basis underlying tolerance to A. ovis . In particular, the unusual haemoglobin polymorphism recorded in Altamurana [6] as well as the other Apulian native sheep breeds [7,12] and the related functional effects may have an adaptive significance related to the local selective pressure exerted by the pathogen and therefore deserve closer examination.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, breeds traditionally reared below the 41° parallel generally display a good tolerance to TBDs [3]. Due to this feature, breeds from these areas are of particular interest to better understand the phenotype "tolerance to TBDs", which is known to be under complex multi-factorial regulation [4,5] and possibly not unrelated to the erythropoietic system [3] as well as to the haemoglobin genetic systems [6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…As highlighted in the above section 4, the phenomenon of tolerance is a broad-based one and possibly not unrelated to the erythropoietic system in different sheep breeds or to the haemoglobin genetic systems (Pieragostini et al, 2003;Pieragostini et al, 2006). Anyway, the success of selection for disease resistance is dependent on correctly identifying the disease agent and the phenotype for disease resistance.…”
Section: Response To Anaplasma Ovis Infection In Experimentally Infecmentioning
confidence: 99%
“…Phenotypic variability induced by parasites is a matter of fact, as impressively exemplified by the high number of haemoglobinopathies in human populations living in malariaendemic areas (Evans & Wellems, 2002). Recalling Feynman's 1 saying that nature repeats itself at every scale, we suggested that the unusual haemoglobin polymorphism recorded in Apulian native sheep breeds and the related functional effects might have an adaptive significance, also being somehow related to the selective pressure of tick borne parasites (TBP) (Pieragostini et al, 1994;Pieragostini et al, 2003;Pieragostini et al, 2006). Based on these considerations, we aimed to define the phenotype of the tick borne diseases in different sheep breeds starting from the one caused by A. ovis, the most common parasite in our area as confirmed by a small survey on sheep TBP performed in 10 farms (throughout Apulia) on 240 individuals.…”
Section: Response To Anaplasma Ovis Infection In Experimentally Infecmentioning
confidence: 99%
See 1 more Smart Citation